Pemanfaatan Batu Gunung Sopai Kabupaten Toraja Utara Dalam Campuran Laston Lapis Aus - Wadyansah Pabisa; Alpius; Charles Kamba (Paulus Civil Engineering Journal, 2021)
This research study is intended to obtain the characteristic test results of the Laston Lapis Aus Sopai mountain rock which aims to determine the characteristics of laston lapis wear. According to the laboratory test, the method used in this research is to perform several characteristic tests, namely coarse aggregate, fine aggat, fiIIer with aspaI, then design the composition and then test MarshaII with a mixture of Laston Lapis Aus and optimal aspaI levels, the remaining MarshaII stability from the mixture is obtained. The result of the research on pavement form materials for the Sopai rock road in North Toraha Regency has fulfilled the 2018 General Bina Marga Provisions, as a layer of the road surface. From the results of the tests that have been carried out for Laston layers of Aus with levels of 5.50%, 6.00%, 6.50%, 7.00% and 7.50%. The results of the Marshall Laston Lapis Aus immersion test for the best bitumen content of 7.50%, the remaining Marshall stability is 99.35%, which is included in the requirements, namely at least 90%.